Extracellular vesicles isolation: a focus on magnetic beads-assisted platforms - Lan, Xinghao; Li, Danyu; Yu, Yancong; Prabhu, Sumedha Nitin; Liu, Guozhen (Frontiers in Bioengineering and Biotechnology, 2025)
Extracellular vesicles (EVs) play a crucial role in cellular communication and hold significant potential for diagnostic and therapeutic applications. However, the efficient isolation of EVs remains a challenge due to their heterogeneity and the presence of contaminating particles. Traditional isolation techniques, such as ultracentrifugation and size-exclusion chromatography, often result in low yield and purity. This review focuses on magnetic bead-assisted platforms as a promising approach to overcome these limitations. Magnetic beads (MBs) offer high specificity, reproducibility, and efficiency in EVs isolation, enhancing their utility in biomedical research and clinical applications. The synthesis and surface modification strategies of MBs are discussed. Additionally, advancements in microfluidic-integrated platforms and multiplex bead-based assays for EVs isolation are explored. The review highlights strategies to optimize EVs capture efficiency and outlines future directions for standardizing magnetic bead-based isolation protocols to improve their applicability in precision medicine.